Mobilità quotidiana e complessità urbana - NUVOLATI, GIAMPAOLO (Studi e saggi, 2007)
The contemporary metropolises are in continual transformation and are characterised by the presence of resident and non-resident populations. Inhabitants, commuters, city users, tourists and businessmen represent segments varying in terms of size, provenance and sojourn within the city, capable of modifying its culture, social and relational fabric, and the morphological urban layout of its multiple components. The objective of this book is to define the complexity of habits of mobility of the various populations and the type of relationship that they have with the places in which they live, work and consume. Attention is similarly focused on the theme of conflicts between different populations, the strategies for meeting needs, and inequalities connected with differentiated opportunities for mobility. The book - which is a version, with updated contents and data, of that published in 2002 entitled Popolazioni in movimento città in trasformazione. Abitanti, pendolari, city users, uomini d'affari, flâneur - also comprises two appendices to which reference can be made to gather data or to sketch out new paths for research into the metropolitan populations.